2014
DOI: 10.1371/journal.pone.0093220
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Passive Smoking in Children

Abstract: BackgroundA significant number of parents are unaware or unconvinced of the health consequences of passive smoking (PS) in children. Physicians could increase parental awareness by giving personal advice.AimTo evaluate the current practices of three Dutch health professions (paediatricians, youth health care physicians, and family physicians) regarding parental counselling for passive smoking (PS) in children.MethodsAll physicians (n = 720) representing the three health professions in Limburg, the Netherlands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The lack of efficient and effective training might be one reason why pediatricians rarely implement effective children’s SHS exposure reduction interventions with smoking parents [ 24 , 25 ]. Similarly, other studies [ 17 , 19 , 24 , 26 ], have shown lack of time to talk with parents as another key barrier to reducing SHS exposure to children and promoting smoking cessation counseling. Researchers have indicated pediatrician’s provision of a brief advice regarding children’s exposure to SHS as an effective first step to make children’ parents quit smoking [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 83%
“…The lack of efficient and effective training might be one reason why pediatricians rarely implement effective children’s SHS exposure reduction interventions with smoking parents [ 24 , 25 ]. Similarly, other studies [ 17 , 19 , 24 , 26 ], have shown lack of time to talk with parents as another key barrier to reducing SHS exposure to children and promoting smoking cessation counseling. Researchers have indicated pediatrician’s provision of a brief advice regarding children’s exposure to SHS as an effective first step to make children’ parents quit smoking [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 83%
“…Future studies on this topic could focus more on how to overcome the defensive barrier of parents to participate in such studies, especially the hard-to-reach population of low social-economic status and/or heavy smokers. A Dutch study demonstrated that doctors infrequently discuss the topic of PS with parents 41 . In the PREPASE study, parents were more willing to participate when they were actively recruited via their physician.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies were cross sectional surveys [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] , including 5287 participants; one study also collected data from electronic healthcare records 32 . Two studies collected data solely from medical records 41,42 .…”
Section: Description Of Included Studiesmentioning
confidence: 99%